Robot motion design using bunraku emotional expressions – focusing on Jo-Ha-Kyū in sounds and movements. (3rd March 2020) - Dong, Ran; Chen, Yang; Cai, Dongsheng; Nakagawa, Shinobu; Higaki, Tomonari; Asai, Nobuyoshi
Abstract : One of the UNESCO intangible cultural heritages Bunraku puppets can play one of the most beautiful puppet motions in the world. The Bunraku puppet motions can express emotions without the so-called 'Uncanny Valley.' We try to convert these emotional motions into robot affective motions so that robots can interact with human beings more comfortable. In so doing, in the present paper, we present a robot motion design framework using Bunraku affective motions that are based on the so-called 'Jo-Ha-Kyū, ' and convert a few simple Bunraku motions into a robot motions using one of deep learning methods. Our primitive experiments show that Jo-Ha-Kyū can be incorporated into robot motion design smoothly, and some simple affective robot motions can be designed using our proposed framework. GRAPHICAL ABSTRACT: